Ad hominem argumentation in politics. (May 2018) - Borovali, Murat
A healthy and robust public political culture is generally regarded as being of utmost necessity for the maintenance of a stable democratic environment. Especially when a country is facing significant challenges and is in the process of devising and implementing radical reforms, the presence of satisfactory collective deliberation can ensure durability and stability. This article will focus on one type of argumentation that stands in the way of such healthy deliberation. It will explore the various forms that ad hominem arguments take and consider the harmful consequences of their wide prominence in the political culture of the country.